(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Introduction: Nosocomial infections are one of the leading causes of morbidity and mortality among hospitalized patients. An intensive care patient has five to seven fold higher risk of infection. The rate of nosocomial infections in the ICU is rising, mainly because of increasing use of invasive procedures for therapeutic interventions. The aim of the study was to know the bacterial profiles and determine the sensitivity pattern of the isolates in the intensive care unit of Chittagong Medical College Hospital during June’2017 to August’2018. Materials and methods: A prospective study was conducted in the ICU of those patients who were clinically suspected of having acquired infection. The clinically sus- pected laboratory samples were collected from the patients and subjected to testing and antibiotic sensitivity. Results: The rate of ICU associated infection was 9.22%%. Respiratory tract infection was the most common infection (58.44%). The predominant isolate was Klebsiella pneumoniae (36.92%) followed by Acinetobacte (23.03%) Pseudomonas aeruginosa (20%). Klebsiella pneumonia was mostly sensitive to Meropenam and Amikacin, then Colistin and Acinetobacter to the Cotrimoxazole. Conclusion: Klebsiella pneumoniae was the major organism identified as the causative agent of nosocomial infection and showed higher susceptibility to Meropenam. Regular surveillance of antibiotic susceptibility pattern and judicious use of antibiotics are very important in ICU for controlling resistance. JCMCTA 2020 ; 31 (2) : 95-98